SOME QUESTIONS OF IMPROVING LABORATORY WORKS ON THE METHOD OF TEACHING BIOLOGY (Scientific journal of the Fergana State University, 2023)
This article highlights the importance of improving the laboratory work of the course of biology teaching methods in improving the quality and efficiency of training future biology teachers on the example of the section "Animals"